Profit Sharing And The Role Of Professional Partnerships* - Levin, Jonathan; Tadelis, Steven (Quarterly Journal of Economics, 2005)
We compare the costs and benefits of profit-sharing partnerships relative to the corporate form of organization. We show that organizing as a partnership can be desirable in human-capital intensive industries where product quality is hard to observe. The theory explains the relative scarcity of partnerships outside of professional service industries such as law, accounting, medicine, investment banking, architecture, advertising, and consulting. It also sheds light on features of partnerships such as up-or-out promotion systems, the use of non-compete clauses, motives for profit sharing as well as recent trends in professional service industries